Outcome of treatment with carfilzomib before and after treatment with daratumumab in relapsed or refractory multiple myeloma patients. Issue 4 (2nd August 2021) - Højholt, Karen Louise; Gregersen, Henrik; Szabo, Agoston Gyula; Klausen, Tobias Wirenfeldt; Levring, Mette Bøegh; Preiss, Birgitte; Helleberg, Carsten; Breinholt, Marie Fredslund; Hermansen, Emil; Rahbek Gjerdrum, Lise Mette; Bønløkke, Søren Thorgaard; Nielsen, Katrine; et al.
Abstract: Real world evidence is important since most patients cannot be included in randomized clinical trials (RCTs). In a nationwide, cohort of relapsed/refractory multiple myeloma patients treated with daratumumab ( N  = 635), we retrospective studied patients treated with carfilzomib ( N  = 251). Data were collected by audit of medical records. We compared characteristics of patients treated with carfilzomib before daratumumab (Car‐Da; N  = 150) and after daratumumab (Da‐Car; N  = 101) with those not treated with carfilzomib ( N  = 384). Furthermore, we examined effectiveness and safety of carfilzomib. The group of patients treated with carfilzomib differed from patients not treated with carfilzomib in the following parameters: They were younger, more were treated up‐front with high dose melphalan and autologous stem cell transplantation (HDM‐ASCT)and had relapse within 18 months thereafter, and more had high‐risk cytogenetic abnormalities (CA) and amplification 1q (amp1q). In patients treated with Car‐Da, 30.3% had high‐risk CA and 30.1% had amp1q and in Da‐Car it was 43.3% and 41%, respectively. In the Car‐Da cohort, 34.4% experienced early relapse after HDM‐ASCT versus 47.4% in the Da‐Car cohort. The percentage of patients with very good partial remission was higher in patients treated with Car‐Da compared to Da‐Car (31.7% vs. 17.4%). The median duration of treatment and time to next treatment (TNT) of Car‐Da/Da‐Car were 4.6/4.3 months and 7.1/4.3 months and only a trend toward superior TNT for Car‐Da was found ( p  = 0.06). Toxicity of carfilzomib was the same as reported in RCT. A similar poor TNT of daratumumab was found when used before (5.6 months) or after carfilzomib (4.9 months). In this cohort of patients with sequential treatment with carfilzomib and daratumumab or vice versa, a high percentage of patients were high‐risk by CA, amp1q, and early relapse after HDM‐ASCT. Outcome of Car‐DA and outcome of Da‐Car were equally poor. These patients should be considered for new promising treatment strategies.